EXTERNAL FEEDBACK, ORGANIZATIONAL TRAINING AND ORGANIZATIONAL PERFORMANCE: A QUALITATIVE INQUIRY - Winarto Winarto (Jurnal Ilmiah METHONOMI, 2016)
The goal of HRM practices is to increase productivity and organizational performance. Training as one of the HRM practices can improve organizational performance through enhancing organizational human capital and organizational knowledge. This research examines the interaction between training and external feedback, which might strengthen the relationship between training and organizational performance in a positive way. Using a qualitative research approach, the research had been done in a service company mainly focus on delivery services. After interviewing the key people in the organization, we concluded that external feedback given by the supervisors or colleagues can strengthen the relationship between training and organizational performance. Finally, practical implication and research limitations are discussed.